Evaluation of endodontic treatments performed by hiring student (Research, Society and Development, 2022)
The clinical-radiographic control, after endodontic treatment, allows to evaluate and prove the results of endodontic therapy, classifying it as success or failure. Endodontic success can be defined as the final result of endodontic therapy, when the tooth is clinically asymptomatic, functional and without radiographic pathology. This study aimed to evaluate the quality of endodontic treatment performed by undergraduate students at the Faculty of Dentistry, University of Pernambuco, Brazil. The dental records of the sample included all patients seen in 2000 and 2022. Chi-square and Fisher's exact tests were used to calculate the significance level set at 5%. The sample size was 219 patients and it was possible to verify the success in most treatments, observing a percentage of 85.4% (188 patients) and failure in only 31 patients (14.2). Regarding the apical limit of the root canal system obturation, the treatment success was much higher when the obturation was in the apical foramen and in the CDC, 92.0 and 91.4%, respectively and the worst result in cases of sub-obturation , 70.0%, with a statistically significant difference. It is concluded that there was a high percentage of success in endodontic treatment performed by undergraduate students at the Faculty of Dentistry of Pernambuco, indicating that academics are receiving quality education.